ТЯГОВА ЕЛЕКТРОМЕХАНІЧНА СИСТЕМА ТРОЛЕЙБУСА У РАЗІ ЖИВЛЕННЯ ВІД НИЗЬКОВОЛЬТНОЇ АКУМУЛЯТОРНОЇ БАТАРЕЇ З ВИКОРИСТАННЯМ ПІДВИЩУВАЛЬНОГО DC/DC ПЕРЕТВОРЮВАЧА - Ковбаса, С.М.; Вербовий, Ю.В.; Гупалов, К.А. (Інститут електродинаміки НАН України, Київ, 2025)
This paper deals with an electromechanical system of the trolleybus which is fed by low voltage on-board battery using boost DC/DC converter. Peculiarities of the use of the boost converter to power up field-oriented controlled traction electric drive were studied. It is shown that already existing primary stage of the traction electric drive can be used to implement boost DC/DC converter. Control algorithms for stabilizing the voltage of the direct current link and direct field-oriented control of the torque and the flux of induction motor are presented, which can be applied to implement the maneuvering operation mode of trolleybus. Proposed electromechanical system was tested by the mathematical modeling, taking into account the pulse width modulation in the DC/DC converter, as well as the parameters of the single-section trolleybus and the forces of resistance to its movement. It is shown that when the battery current is limited to 200 A and the voltage of the direct current link (the output voltage of the DC/DC converter) is stabilized at 250 V, unloaded trolleybus can reach a speed of 12 km/h on a flat asphalt surface. The results of the study of the achievable speed of the vehicle at different values of the battery current limit and the level of the DC link voltage task are also presented in the paper. The results of the performed research can be used in the development of new and modernization of existing electromechanical systems of trolleybuses. References 11, figures 8.